OPTIMALISASI POTENSI MASJID SEBAGAI BASIS PENGUATAN EKONOMI MIKRO SYARIAH DI BMT MESJID ALMUHSININ CIAMIS - Ganjar Santika; Iip Miftah Fauzi; Wida Lisnawati (Universitas Siliwangi, 2019)
The mosque is a religious infrastructure which mostly carries out activities related to devotion to Allah, because the function of the mosque has four main functions, namely as a place of worship, social, educational and economic. Therefore the mosque is not only a place to carry out worship to The Creator, but at the same time facilities muamalah activities. This study aims to determine, describe and analyze the optimization of the role of the al-Muhsinin mosque as a place of worship that is integrated with the service of the people as strengthening the economy of rural communities. This research was conducted with a qualitative approach with the method of observation and interviews with informants who were considered to understand the system applied to the Cisontrol village mosque-based economy. Data analysis used is interactive data analysis. The main purpose of the establishment of a mosque-based economy in the village of Kubang Cisontrol village is to meet the needs of the community for food needs before the month of Ramadan and various other goods so that it does not fall into the ribawi gorge